The International course in Brodeaux (Fiep Bulletin - online, 2015)
The International course Physical Education, organized by the ”F.F.G.E.G.V.” at the C.R.E.P.S. in Cordeaux, from the 3rd to the 10th September, has had the greatest success, according to tradition.